Anaerobic power profiles for track and field - Johnson, Michael J. (My University, 2008)
This research sought to determine the importance of lower and upper body muscular power in relation to performance in track and field events. During the late competitive outdoor season, 32 male and female track and field athletes at an NCAA Division III institution were tested using a 30 second standard Wingate Anaerobic Test (WAT) on a Monarch cycle ergometer and a modified WAT on a Monarch cycle ergometer to measure lower body and upper body power, respectively. Prior to testing, the investigator collected data concerning age (yrs), height (cm), weight (kg) and gender. Each track and field participant?s personal records (PR?s) were recorded for up to three of the subject?s best events. Subjects then performed the standard WAT and modified WAT during a single exercise session. Data was then analyzed in Microsoft Excel spreadsheets to determine average performance and correlation relationships between power outputs and performance. Correlation analyses were based upon the relationship between performance (PR in seconds or meters) and peak power, average power, minimum power, and power drop in W/kg for the standard and modified Wingate. The data showed that the short sprint events presented power outputs that indicated a high level of anaerobic power (i.e., short sprints, sprint hurdles, jumps); whereas, longer sprints and middle-distance/distance events showed lower anaerobic power levels. Correlation analysis showed that subjects who participated in the short sprint events tend to have weaker correlations with respect to lower and upper body power for all variables (peak power, average power, minimum power, and power drop) when compared to subjects who participated in events of increasing distances. Short sprint event subjects showed moderate to strong correlations (0.3-0.8+), 800-meter event runners up to 5,000/10,000-meter event runners had nearly perfect correlations (0.9+) in relation to lower and upper body anaerobic power. Vertical jumpers (high jump and pole vault) showed similar correlations to long sprinters (400-meters/400-meter hurdles); whereas, horizontal jumpers (long jump and triple jump) showed correlations similar to that of short sprinters. The purpose of this study was to determine whether a significant amount of training should be spent developing anaerobic lower and upper body power depending on event specialization. The study indicated that while these variables are important, they are not single-handedly the main training factor. Subjects who participate in the power driven events demand high anaerobic power and more endurance driven events possess higher aerobic power. Training one energy system or another (i.e., aerobic versus anaerobic); is not the sole factor to determine performance.
Date original was created: August 11, 2008. This file was last viewed in Adobe Reader 8.0
Keywords: Track and field athletes--Training of; Physical fitness--Measurement; Energy metabolism--Measurement